TGF-β1-Mediated Leukocyte Cell-Derived Chemotaxin 2 Is Associated With Liver Fibrosis in Biliary Atresia - Zhao, Jinfeng; Xu, Xiaodan; Gou, Qingyun; Zheng, Qipeng; Ge, Liang; Chen, Lingzhi; Zhang, Cong; Ma, Hui; Lin, Shuxiang; Hu, Xiaoli; Zhan, Jianghua (Frontiers in Pediatrics, 2022)
Objective: Biliary atresia (BA) presents as a severe infantile cholangiopathy disease, characterized by progressive liver fibrosis and the resulting poor prognosis. Leukocyte cell-derived chemotaxin 2 (LECT2) was proposed as the key gene associated with hepatic fibrosis in BA, but the molecular mechanism is unclear. This study aims to investigate the function of LECT2 in BA. Methods: Fifty-three patients were enrolled in this study, thirty-six patients with BA, and seventeen control patients with cholestasis, including congenital biliary dilations, biliary hypoplasia, and inspissated bile syndrome. The role of LECT2 in BA was analyzed with histological and cytological tests. The correlation between LECT2 and infiltrating immune cells was further analyzed by bioinformatics. The data were conducted by correlational analyses and ROC curves. Results: LECT2 was high expressed in BA infants and positively related with fibrosis (0.1644 ± 0.0608 vs. 0.0779 ± 0.0053, p<0.0001), (rs= 0.85, p<0.0001). Serum levels of LECT2 showed high distinguishing features for BA patients with the AUC of 0.95 (95% CI: 0.90 to 1.00). CD163 was highly expressed in the aggravation of fibrosis (0.158 ± 0.062 vs. 0.29 ± 0.078, p＜0.0001), the expression of LECT2 was positively correlated with the accumulation of CD163+ macrophages (r=0.48, p=0.003). The bioinformatic analysis also showed that LECT2 was positively correlated with macrophages M2 (r=0.34, p=0.03). TGF-β1 and CD163 colocalized to the portal area in the livers of BA patients. Moreover, TGF-β1 upregulated the expression of LECT2. Conclusions: LECT2 is highly expressed in both BA liver tissue and serum, and serum LECT2 is a potential diagnostic biomarker of BA. Meanwhile, TGF-β1 is secreted by macrophages to regulate LECT2 associated with BA liver fibrosis.